Respiratory training as strategy to prevent cognitive decline in aging: a randomized controlled trial - Ferreira, Leandro; Tanaka, Katia; Santos-Galduroz, Ruth Ferreira [UNESP]; Fernandes Galduroz, Jose Carlos (Dove Medical Press Ltd, 2015)
Background: Inadequate oxygenation may cause lesions and brain atrophy during aging. Studies show a positive association between pulmonary function and the cognitive performance of individuals from middle age on.Objective: To investigate the effect of aerobic physical exercises and respiratory training on the blood oxygenation, pulmonary functions, and cognition of the elderly.Design: This was a randomized and controlled trial with three parallel groups. A total of 195 community-dwelling elderly were assessed for eligibility; only n=102 were included and allocated into the three groups, but after 6 months, n=68 were analyzed in the final sample. Participants were randomized into a social interaction group (the control group), an aerobic exercise group (the "walking" group), or a respiratory training group (the "breathing" group). The main outcome measures were the Wechsler Adult Intelligence Scale, Wechsler Memory Scale, Wisconsin Card Sorting Test, respiratory muscular strength, cirtometry (thoracic-abdominal circumference); oxygen saturation in arterial blood (SpO(2)), and hemogram.Results: No differences were observed for any of the blood parameters. Aerobic exercise and respiratory training were effective in improving the pulmonary parameters. Better cognitive performance was observed for the breathing group as regards abstraction and mental flexibility. The walking group remained stable in the cognitive performance of most of the tests, except attention. The control group presented worst performance in mental manipulation of information, abstraction, mental flexibility, and attention.Conclusion: Our results showed that both the walking and breathing groups presented improvement of pulmonary function. However, only the breathing group showed improved cognitive function (abstraction, mental flexibility). The improvement in cognitive functions cannot be explained by blood parameters, such as SpO(2), erythrocytes, hemoglobin, and hematocrit.
Keywords: Breathing exercises; Cognition; Exercise